CONTENT COMPONENTS OF STUDENTS’ VALUE ORIENTATIONS - I. A. Bakushkin; I. M. Ilyicheva (Вестник университета)
The article considers theoretical aspects of values and value orientations. The paper gives results of their empirical research among 1st–3rd year students learning pedagogy. The authors discuss various approaches to the understanding of values and value orientations, their classification in domestic and foreign psychology, the place of values in the structure of the individual, as well as the significance of values in the structure of the individual and the need to allocate a separate group of priority values – universal values. The study presents the results of an empirical study of terminal and instrumental values (the M. Rokich method in the modification of D. Leont’ev). The paper highlights groups of students depending on value orientations, analyses similarities and differences in most important and less desirable terminal and instrumental values, which different groups have.